2010
DOI: 10.1017/s0033822200046282
|View full text |Cite
|
Sign up to set email alerts
|

Centuries of Marine Radiocarbon Reservoir Age Variation Within Archaeological Mesodesma Donacium Shells from Southern Peru

Abstract: ABSTRACT. Mollusk shells provide brief (<5 yr per shell) records of past marine conditions, including marine radiocarbon reservoir age (R) and upwelling. We report 21 14 C ages and R calculations on small (~2 mg) samples from 2 Mesodesma donacium (surf clam) shells. These shells were excavated from a semi-subterranean house floor stratum 14 C dated to 7625 ± 35 BP at site QJ-280, Quebrada Jaguay, southern Peru. The ranges in marine 14 C ages (and thus R) from the 2 shells are 530 and 170 14 C yr; R from indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Previous research has documented significant intrashell variability in 14 C content in mollusks from California and Peru Jones et al 2007Jones et al , 2010 and more limited variability in specimens from Georgia's Atlantic coast (Thomas et al 2013). The variability in 14 C from Peru and California is thought to stem largely from seasonal variations in coastal upwelling, but both Culleton Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented significant intrashell variability in 14 C content in mollusks from California and Peru Jones et al 2007Jones et al , 2010 and more limited variability in specimens from Georgia's Atlantic coast (Thomas et al 2013). The variability in 14 C from Peru and California is thought to stem largely from seasonal variations in coastal upwelling, but both Culleton Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported short‐term fluctuations of Δ R , for example at Fanning Island in the equatorial Pacific (Grottoli et al , ) and off the coast of Peru (Jones et al , , ). Short‐term fluctuations of Δ R have also been reported in the Kuroshio region, including at Ishigaki Island (Hideshima et al , ; Araoka et al , ), although the data used in these studies are not continuous spatially or temporally, which makes it difficult to draw conclusions about the cause of the fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…For ancient periods, variations of mean paleoupwelling intensity can be indicated by variations of marine reservoir age estimated by the radiocarbon analysis of contemporaneous marine shells and plant remains Ortlieb et al, 2011]. However, this method has significant uncertainties because of potential old wood effect and intrashell variability of reservoir age [Jones et al, 2007[Jones et al, , 2010. We propose here to use an alternative paleoenvironmental archive that would yield independent estimates of the coastal upwelling intensity and insights into seasonal scale productivity processes.…”
Section: Introductionmentioning
confidence: 99%